Splinting for thumb carpometacarpal osteoarthritis: protocol for a feasibility randomized controlled trial. (3rd May 2020) - Buhler, M.; Chapple, C. M.; Stebbings, S.; Adams, J.; Gwynne-Jones, D.; Baxter, G. D.
Abstract: Background: Evidence for the use of splints to reduce pain and improve function and quality of life in thumb carpometacarpal osteoarthritis (CMC OA) is sparse and poor despite recommendations by international guidelines. Objective: To outline the protocol for a study designed to determine the feasibility of conducting a fully powered pragmatic randomized controlled trial (RCT) comparing soft splint vs no splint for thumb CMC OA. Methods: The proposed pragmatic, assessor-blinded, and partial participant blinded parallel-group feasibility RCT will recruit 30 adults with thumb CMC OA and randomise to: splint intervention or usual care control. Randomization will be stratified by hand dominance. Primary feasibility outcomes are recruitment rate over a 4-month period, retention rate at 6 months, intervention acceptability, and rate of adverse events. Study costs, intervention fidelity, and clinical outcomes will also be evaluated. Measurements will be collected at baseline, 4 weeks, and 6 months post-initiation of treatment. This trial has been registered with the Australian New Zealand Clinical Trials Registry (ANZCTR): ACTRN12618001639213. Major Findings : N/A. Conclusions: If shown to be effective, soft off-the shelf splints would be a good first-line non-pharmacological, non-surgical option for thumb CMC OA as prescribed by health professionals or accessed directly by patients. This feasibility study will inform a future, fully powered RCT as evaluated by success of the recruitment strategy; assessment time and acceptability; implementation and evaluation of 'usual care'; and intervention procedures and adherence.